PENINGKATAN EKONOMI PETANI MELALUI PENDAMPINGAN PEMASARAN ONLINE DAN OFFLINE PADA USAHA BAWANG MERAH GORENG DI KECAMATAN RUBARU SUMENEP - Mohammad Hosnan; Ubaidillah; Ach. Khatib (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2024)
The focus of this service is that it is hoped that fried shallot business actors in Rubaru District will have positive developments in the field of online marketing based on information technology and maintain offline marketing. This service uses Participatory Action Research approach where the service actively helps and directs the community to move, but is integrated into the community so that intensive and massive collaboration is built to develop the assisted community. The results of this service activity include: (1) Red onion product innovation, apart from being sold raw, it is also fried and made into shallot snacks. (2) The marketing strategy adopted is offline marketing assistance and online marketing training, as well as registering for Integrated Online Licensing (Online Single Submission/OSS), optimizing Shopee, Tokopedia and Bukalapak accounts, optimizing Facebook, Instagram, Youtube and TikTok social media accounts, and migrating Regular WA to Business WA. (3) The economic growth of fried shallot business actors is relatively increasing due to the increasing number of transactions carried out, both offline and online